Evaluation and utilization of eggplant germplasm (Solanum melongena L.) in the development of high yielding and quality hybrids - Datta, Debi Rani (2022)
Eggplant ranks the fifth economic important crops among the Solanaceae family after tomato, potato, chilli, and tobacco. In Malaysia eggplant production is relatively low (17 t/ha) compared to other neighbouring countries (i.e. China 46.28 t/ha and Thailand 35.25 t/ha). One of this crop's major production limitations is the lack of high-yielding and high-quality variety. Hence, there is a need to step up the current eggplant production to meet the continuously growing demands. Therefore, the specific objectives of this study were to determine the genetic diversity of eggplant accessions using morphological data and simple sequence repeat (SSR) molecular markers. In addition, to identify superior parents and their hybrids based on general (GCA) and specific combining ability (SCA), and to estimate heterosis values for yield trait and yield components. The study locations were UPM field Ladang 15 and Ladang 10, Serdang, Selangor, Malaysia. This study consisted of four experiments, where the first experiment was done to evaluate 56 accessions in an open research field. All the traits showed high heritability and genetic advance values, indicating that these traits can easily be transferred from parents to their progenies. Dendrogram was constructed based on yield performance, and the genotypes were clustered into seven groups. From this study, the accessions from clusters II, III and IV were selected, which having a high number of fruits per plant. In the second experiment, out of 102 SSR markers, 16 were found polymorphic. The selected markers reveal a high level of polymorphism within the population and low polymorphism level among populations. In the third experiment, 27 accessions selected from previous study were further evaluated on the field to select the best genotype based on quantitative and qualitative traits performance. From this evaluation, a total of 11 accessions (BB1, BT13, BM9, BB26, BB31, BM5, BB23, BT17, BB12, BT6 and BT15) were selected as parents for hybridization through 11×11 half diallel method. The hybrids (55), parental lines (11) and check varieties (3) were evaluated over two locations followed by randomised complete block design (RCBD) with three replications to evaluate the hybrids performance and to estimate gene effects and combining ability of 15 morphological and biochemical traits. The analysis of variance indicated highly significant differences between the environments and interaction of genotype and environment for all the traits, except for fruit length to width ratio. Additive gene effects were significant for the inheritance of these traits and the expression of additive genes were greatly affected by environments. The general combining ability (GCA) was greater than their respective specific combining ability (SCA) for all traits except for fruit yield per plant. High values of GCA and SCA effects for characters of interest were dispersed among genotypes. From this evaluation, it was observed that the best parental line was BT15 based on days to first flowering, number of fruits per plant, total soluble solids (TSS) and total phenol content. Besides, the parent BM5 showed good general combining ability effects for fruit yield per plant, fruit length and fruit length to width ratio, while the parent BB1 performed good general combining ability for fruit diameter, fruit girth and average fruit weight. On the other hand, the hybrid BT6 × BT15 showed bearing early flowering with high total phenol content, while the hybrid BM9 × BB26 had high fruit yield per plant and total soluble solids. In addition, hybrid BM9 × BB1 had a high fruit diameter and average fruit weight. These superior eggplant hybrids are recommended for a large-scale evaluation and then for commercial cultivation by local vegetable farmers.